Contemporary perspectives on Lacanian theories of psychosis - Redmond, Jonathan D. (Frontiers in Psychology, 2013)
Abstract: In contemporary Lacanian psychoanalysis, Verhaeghe’s theory of actualpathology / psychopathology in psychosis and the Millerian idea of “ordinary psychosis” provide diverging conceptual approaches to psychosis. In this paper, the two approaches to psychosis are examined with a particular emphasis on “mild psychosis” and compensatory mechanisms. Despite the shared focus on similar clinical phenomena, particularly body disturbances, these two theories provide different explanations of psychosis. Verhaeghe’s theory of psychosis is a synthesis of Lacanian theory, Freud’s idea of actual neurosis and psychoanalytic attachment concepts. Moreover, these ideas are situated in the “schizophrenia / paranoia dichotomy” an important heuristic device utilised in clinical practice with psychosis. In contrast, the Millerian field of ordinary psychosis aims to broaden the idea of psychosis by reviving the idea of “mild psychosis” and the different forms of stabilisation possible in psychosis. Clinicians adapting the idea of ordinary psychosis aim to rethink pivotal Lacanian concepts - “untriggered” psychosis and stabilisation - beyond the scope of the schizophrenia / paranoia dichotomy. Although the idea of ordinary psychosis requires further development, it promise greater utility than Verhaeghe’s model, as it provides a broader and more nuanced approach to the complex vicissitudes of triggering and restitution in psychosis.